The Limits of Proxy Decision Making: Undertreatment - Gillick, Muriel R. (Cambridge quarterly of healthcare ethics, 1995)
With the passage by virtually every state legislature of healthcare proxy laws, the medical profession increasingly can expect to rely on the participation of surrogates in making decisions on behalf of incompetent patients. Several concerns about the legitimacy of proxy decision making have been discussed in the ethical and general medical literature: the lack of concordance between the views of patients and their surrogates have been documented on multiple occasions, and cases of abuse by proxies or potential conflict of interest have been reported. Another dilemma that deserves discussion arises when proxies demand withdrawal of treatment that physicians and nurses regard as essential to the wellbeing of the patient. The following case highlights this dilemma.